Campur Kode dalam Pembelajaran Bahasa Indonesia Kelas VII SMP Negeri 1 Ruteng - Giovanni Battista Agung; Margareta Sofyana Irma Kaet; Blandina Wenika Djawa (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to analyze the forms of code-mixing, its triggering factors, and the impact of its use in Indonesian language instruction for seventh-grade students at SMP Negeri 1 Ruteng. This study employs a qualitative approach with a descriptive design. The research subjects were seventh-grade teachers and students who are bilingual speakers (Manggarai and Indonesian). Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that code-mixing occurs in the form of words and phrases, with a predominance of word-level code-mixing. Triggers for code-mixing include efforts to create a friendly atmosphere, providing examples, explaining material, asking questions, and responding to answers, with creating a friendly atmosphere being the most dominant factor. The findings also show that the practice of code-mixing does not have negative effects but rather aids student comprehension and fosters a more comfortable learning environment. This study contributes to the development of educational sociolinguistic research by demonstrating that code-mixing can function as an effective communication strategy in learning within a bilingual environment. Furthermore, the results of this study provide practical implications for Indonesian language teachers to utilize code-mixing appropriately as part of their teaching strategies without neglecting the proper and correct use of the Indonesian language. Keywords: code-mixing; language learning; bilingual; classroom interaction; sociolinguistics